The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8ra03369b
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted metabolite profiling and specific targeted discrimination strategy for quality evaluation of Cortex Phellodendri from different varieties

Abstract: Non-targeted metabolite profiling and specific targeted discrimination strategy coupled with pattern recognition to differentiate the two varieties in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The possible metabolic pathway of major compounds is indicated in Figure 8. Most of the metabolites remained the skeleton structural characteristics which absorbed in blood [17], the study of fragmentation pathways accelerated the authentication of metabolites from WSYGD in plasma.…”
Section: Characterization Of Mouse Metabolites Of Wsygdmentioning
confidence: 99%
“…The possible metabolic pathway of major compounds is indicated in Figure 8. Most of the metabolites remained the skeleton structural characteristics which absorbed in blood [17], the study of fragmentation pathways accelerated the authentication of metabolites from WSYGD in plasma.…”
Section: Characterization Of Mouse Metabolites Of Wsygdmentioning
confidence: 99%
“…Phellodendri Amurensis Cortex and Phellodendri Chinensis Cortex are obtained from the same genus but different varieties: Phellodendron amurese and P. chinense correspondingly. The discrimination research with PLS‐DA indicated that 17 prototype constituents and 22 metabolites were synergetic contributions for the group separation of the two types of medicines 68 …”
Section: Applications Of Chemometrics In Tcmmentioning
confidence: 99%